ADVANCEMENTS IN CHEMICAL-TOXICOLOGICAL ANALYSIS METHODS FOR NASVAY: INSIGHTS FROM BIOLOGICAL FLUID COMPOSITION - Qodirov Zokirjon Sulaymon o’g’li; F.S. Jalilov (Лучшие интеллектуальные исследования, 2024)
Abstract: To date, the most common form of smokeless tobacco in Central Asia, in particular in Uzbekistan, is nosvoy. In Uzbekistan, more than 23% of men consume nosvoy. Exposure to nos can lead to the development of cancer in the mucous membranes and many other negative consequences. Nos consists of a mixture of substances with a complex composition of dark green or yellowish green. Basically, this product is prepared in different ways, without observing the sanitary rules in the home environment. It is a saying that someone who sees the method of its preparation, knows what substances it contains, refuses to smoke nos.Nasvay, a traditional smokeless tobacco product, poses significant public health concerns due to its association with various adverse health effects, including addiction and cancer. Analyzing the composition of biological fluids provides valuable insights into the chemical-toxicological profile of Nasvay and its potential health impacts. This article reviews recent advancements in analytical methods for assessing Nasvay constituents in biological fluids, highlighting the importance of comprehensive toxicological analysis in understanding its physiological effects. By integrating innovative techniques such as mass spectrometry, chromatography, and biomarker analysis, researchers can elucidate the complex interplay between Nasvay components and biological systems, informing regulatory efforts and public health interventions.